Reef Conservation off the Hook: Can Market Interventions Make Coral Reef Fisheries More Sustainable? - Cramer, Katie L.; Kittinger, John N. (Frontiers in Marine Science, 2021)
The overexploitation of coral reef fisheries threatens the persistence of reef ecosystems and the livelihoods and food security of millions of people. Market-based initiatives to increase fisheries sustainability have been widely implemented in industrialized commodity fisheries, but the suitability of these initiatives for coral reef fisheries has not been systematically investigated. Here, we present a typology of market-based interventions and coral reef fisheries sectors and identity promising approaches for each fishery archetype. For high value, export-oriented reef fisheries that are highly unsustainable (live reef food fish and dried sea cucumbers), traditional regulatory efforts including trade restrictions will be most effective. For high-value, export-oriented fisheries for highly fecund invertebrates (lobsters and mollusks), certification and ratings efforts, fishery improvement projects, and sustainable purchasing commitments can improve fishing practices and increase fisher market access and revenue. For lower-value fisheries targeting species for domestic or regional consumption, sustainable purchasing commitments among local buyers, consumer awareness campaigns, and local certification and ratings schemes hold promise for shifting attitudes toward sustainability and increasing food security for local communities. Finally, fisher empowerment efforts including direct access to local markets and market information, training on improved post-harvest methods, and formation of fisher associations hold promise for increasing fisher incomes, reducing wasteful catch, increasing food security, and de-incentivizing unsustainable practices. Despite the potential of market-based interventions, specific approaches must be carefully tailored to the ecological and social reality of these systems, including the inherent unsustainability of commercial coral reef fisheries, the limited capacity for fisheries governance, the limited financial support of market-based initiatives, and the threatened status of coral reef ecosystems globally.